EVALUASI UPAH LEMBUR SATPAM OUTSOURCING PADA KOPERASI SIMPEDA JAYA - Heriyanto, Vetty Suknaryana, Titin Ruliana (EKONOMIA, 2015)
The purpose of this study was to evaluate the data for the calculation of overtime pay outsourced security guards who shelter under Simpeda Jaya Cooperative in accordance with the calculation according to the Ministry of Manpower Decree No: KEP.102/MEN/VI/2004.            Based on the analysis and discussion, the conclusions of this study :1.      Simpeda Jaya Cooperative in apply overtime still does not meet standards that have been adopted by the Government which refers to the Ministry of Manpower Decree No: KEP.102/MEN/VI/2004.2.      The difference between the calculation of overtime pay Simpeda Jaya Cooperative to the standard that has been adopted by the Government which refers to the Ministry of Manpower Decree No: KEP.102/MEN/VI/2004 lies in the placement of overtime hours caused by a lack of available labor, while a lot of data outsourcing security guard overtime BPD Kaltim Samarinda to be done, so lack of effectiveness in the work resulting in the difference in the determination of the multiplication result in differences in the calculation of overtime and overtime.3.      In Overtime Calculation Period February 2013 Simpeda Jaya Cooperative has a difference of Rp 608.699,00 overpayment of calculations according to the Ministry of Manpower Decree No: KEP.102/MEN/VI/2004.Companies should maintain the existing work discipline and always obey all the regulations already in force and increase the effectiveness of employees in work. Based on the analysis and discussion above it can be concluded how to calculate the overtime rate of outourcing security in Simpeda Jaya Cooperative has not been in accordance with the Decree of the Ministry of Manpower Decree No: KEP.102/MEN/VI/2004, so the hypothesis is proven by the outhors received.